Assessing progress against nutrition status targets - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
This chapter tracks countries’ progress in improving the nutrition status of their populations. It begins by assessing countries’ progress at meeting the targets for reducing undernutrition by 2025, set by the World Health Assembly (WHA) in 2012 as in the Global Nutrition Report 2014, we apply the global targets to each country to assess whether it is on or off course to meet the 2025 global targets. In this year’s report we use more fine-grained assessments of Progress that provide more information than whether a country is simply on or off Course. In addition we present new data that describe progress made at the subnational Level in India—the country with the largest burden of undernutrition.